A laboratory model of marine snow: Preparation and characterization of porous fiber particles. (4th September 2015) - Dörgens, Anna L.; Ahmerkamp, Soeren; Müssig, Jörg; Stocker, Roman; Kuypers, Marcel M. M.; Khalili, Arzhang; Kindler, Kolja
Abstract: A method is described to prepare laboratory models of marine snow flocks using textile fibers to facilitate settling and mass transfer experiments under hydrodynamically well‐defined conditions. A simple and effective roll‐agglomeration process is introduced to fabricate macro‐scale (up to centimeter‐size) fiber particles, with predefined porosity, permeability, and excess density. Hydrodynamic similarity with natural marine snow aggregates was confirmed by measurements of porosity, permeability and settling velocity measurements. The assessment is completed by an analysis of the performance of the fabrication method. The fiber particles generated via this method can be used to advance our understanding of the hydrodynamics underlying settling dynamics and the associated mass transfer.